(3LhGH SDGd QLd JThT ef LgI GdSHHs
(3ChdgG (B:s
(3GdMeO ddg GeG HYO abO cGf hUdfi cJGHce hPcQJe ajg JThT MGdce ef LgI GdSHH hGfce de JhGabhG Ydi JQcg s
(3BNQgG (B:s
(3ef GdMcGjGJ YHQ ddeYJHQjf hHdGZ ddYGHOjf habfG QHfG dPdc s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdESchQjGd s
Keywords: (3GdJUha hGdBOGH GdTQYjIs